LIVING QUR’AN: IMPLEMENTING QUR’ANIC VALUES THROUGH THE TAHFIZH AL-QUR’AN PROGRAM AT AD-DINIYAH ISLAMIC BOARDING SCHOOL PAMEKASAN - Rohmah, Siti (Institut Dirosat Islamiyah Al-Amien Prenduan, 2025)
The Living Qur’an represents a phenomenon of implementing Qur’anic values in daily life through concrete religious practices. This study aims to analyze the implementation of Qur’anic values through the tahfizh Al-Qur’an program at Pondok Pesantren Ad-Diniyah Sumber Batu Blumbungan Larangan Pamekasan. This qualitative research employs a phenomenological approach using data collection techniques including in-depth interviews, participatory observation, and documentation. Research informants comprise the pesantren head, tahfizh program director, three tahfizh teachers, and five active students. The findings reveal that the tahfizh Al-Qur’an program at this pesantren is motivated by the aspiration to produce a generation of hafizul Qur’an and to ground the Qur’an within society. Activities are conducted during morning sessions (05:00-06:40) and afternoon sessions (16:30-17:30) utilizing varied methodologies. The implementation of Qur’anic values is reflected in the cultivation of patience, honesty, and tauhid values through the tahfizh learning process. This research contributes to the development of Living Qur’an studies within the context of pesantren education and provides an applicable model for implementing Qur’anic values.